2007
DOI: 10.1038/nature06306
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory cytokine IL-35 contributes to regulatory T-cell function

Abstract: Regulatory T (T(reg)) cells are a critical sub-population of CD4+ T cells that are essential for maintaining self tolerance and preventing autoimmunity, for limiting chronic inflammatory diseases, such as asthma and inflammatory bowel disease, and for regulating homeostatic lymphocyte expansion. However, they also suppress natural immune responses to parasites and viruses as well as anti-tumour immunity induced by therapeutic vaccines. Although the manipulation of T(reg) function is an important goal of immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
1,586
5
21

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,719 publications
(1,641 citation statements)
references
References 42 publications
29
1,586
5
21
Order By: Relevance
“…Treg can interact with other immune populations via soluble factors and/or via cell-contactdependent mechanisms. Whereas in vivo studies have suggested a major role for soluble factors, such as IL-10 [41], TGF-b [42], or IL-35 [43], most in vitro experiments described a cell-contactdependent mechanism, involving CTLA-4 [44,45], GITR [46], Perforin [33], or Granzyme B [34]. Our data suggest that Perforin/ Granzyme-induced apoptosis does not play a major role in Tregmediated suppression of mouse gd-T-cell activity.…”
Section: Discussionmentioning
confidence: 51%
“…Treg can interact with other immune populations via soluble factors and/or via cell-contactdependent mechanisms. Whereas in vivo studies have suggested a major role for soluble factors, such as IL-10 [41], TGF-b [42], or IL-35 [43], most in vitro experiments described a cell-contactdependent mechanism, involving CTLA-4 [44,45], GITR [46], Perforin [33], or Granzyme B [34]. Our data suggest that Perforin/ Granzyme-induced apoptosis does not play a major role in Tregmediated suppression of mouse gd-T-cell activity.…”
Section: Discussionmentioning
confidence: 51%
“…157 IL-35 was initially described as a Treg-specific cytokine with potent immunosuppressive properties. 158 Studies conducted with IL-35-overexpressing cancer cells reported a role for IL-35 in promoting tumor growth through the suppression of T-cell responses. 159 rejection of breast cancer TSA-IL-12 cells was dependent on CD8 cytotoxic T cells, secreting IFN-g. 43 However, tumor rejection in IL-12-transduced C26 colon carcinoma was partially dependent on GM-CSF-producing CD4 T cells or NK cells, but independent of IFN-g. 46 IL-12-responsive T cells were also ascribed a major role in rejection of tumors of the central nervous system.…”
Section: Mechanisms Of Tumor Protection Through Il-12mentioning
confidence: 99%
“…Furthermore, it has been demonstrated that IL-27 inhibits IL-17 production and EAE by inducing IL-10 from IFN-g 1 T-bet 1 Foxp3 À T cells [110]. Finally, it has recently been reported that IL-35, a heterodimer of Epstein-Barr-virus-induced gene 3 and IL-12p35, which is highly expressed by mouse Foxp3 1 Treg cells [111] and induces IL-10 production by Treg cells, suppresses Th17 cell differentiation and attenuates CIA [112].…”
Section: Regulation Of Il-17-secreting T Cellsmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that IL-27 inhibits IL-17 production and EAE by inducing IL-10 from IFN-g 1 T-bet 1 Foxp3 À T cells [110]. Finally, it has recently been reported that IL-35, a heterodimer of Epstein-Barr-virus-induced gene 3 and IL-12p35, which is highly expressed by mouse Foxp3 1 Treg cells [111] and induces IL-10 production by Treg cells, suppresses Th17 cell differentiation and attenuates CIA [112].The role of TGF-b in regulating IL-17 production by T cells is more controversial. Although TGF-b is secreted by antigenspecific Treg cells, in particular Th3 cells in the gut, and induces peripheral conversion of CD4 1 CD25 À Foxp3 À T cells to CD4 1 CD25 1 Foxp3 1 Treg cells [113], this cytokine has also been shown to function with IL-6 or IL-21 to promote the differentiation of murine and human Th17 cells from naïve CD4 1 T cells in vitro [39][40][41][43][44][45].…”
mentioning
confidence: 99%